Testing the utility of the newest vital sign (NVS) health literacy assessment tool in older African-American patients - Patel, Pragnesh J.; Joel, Steinberg; Rovena, Goveas; Pedireddy, Sailja; Saad, Saima; Rachmale, Ruchi; Shukla, Meghna; Deol, B. Bibban; Cardozo, Lavosier (Patient education and counseling, 2011)
To evaluate utility of the newest vital sign (NVS) which can be completed in 3min compared to the short version test of functional literacy in adults (S-TOFHLA) that takes 7min for health literacy in the older African American patients. We enrolled 62 older (age>65 years) African American patients and administered the NVS and the S-TOFHLA. A score of less than 4 for the NVS and less than 16 for the S-TOFHLA was indicative of limited health literacy. Mean age of our patients was 73.2+7.9 years with an average education level of twelfth grade. Using S-TOFHLA 51% of the subjects were deemed to be sufficiently literate, with a score of 23.0+8.6 compared to 56% on the NVS with a score of 3.0+1.9. The average time for completing the NVS was 11min in our patient population. Based on our data, while health literacy level can be assessed with the NVS its practicality as a quick screening tool in the elderly population appears limited. Knowing the level of patient's health literacy may help physicians deliver health information in the format that patients can understand.